From Anti-EBV Immune Responses to the EBV Diseasome via Cross-reactivity - Kanduc, Darja; Shoenfeld, Yehuda (Global Medical Genetics, 2020)
Sequence analyses highlight a massive peptide sharing between immunoreactive Epstein-Barr virus (EBV) epitopes and human proteins that—when mutated, deficient or improperly functioning—associate with tumorigenesis, diabetes, lupus, multiple sclerosis, rheumatoid arthritis, and immunodeficiencies, among others. Peptide commonality appears to be the molecular platform capable of linking EBV infection to the vast EBV-associated diseasome via cross-reactivity and questions the hypothesis of the “negative selection” of self-reactive lymphocytes. Of utmost importance, this study warns that using entire antigens in anti-EBV immunotherapies can associate with autoimmune manifestations and further supports the concept of peptide uniqueness for designing safe and effective anti-EBV immunotherapies.
Keywords: EBV epitopes; systemic lupus erythematosus; cross-reactivity; autoimmunity; negative selection; self-reactive lymphocytes; pathogenic autoantibodies